Infantile Hemangioma Presenting as Colocolic Intussusception in an Infant Case Report with Review of Pathologic Lead Points. (24th June 2018) - Rais, Rehan; González, Iván; Saito, Jacqueline M.; Dehner, Louis P.
Abstract : Infantile hemangioma (IH) is one of the most common vascular anomalies of early childhood and is usually recognized in the first few weeks to months of life as a solitary cutaneous lesion. This report documents our experience with a GLUT-1 positive IH presenting as the pathologic lead point in a colocolic intussusception in a 10-week-old infant who had no skin lesions. Literature suggests approximately 2% of all children presenting with an intussusception require surgical intervention; however, an IH as the pathologic lead point is unique.